La literatura fantástica y su reescritura en América Latina: un estudio sobre “Color del otoño” de Claudia Hernández - Caamaño Morúa, Virginia (2015)
Through current theoretical proposals on fantastic literature, this article analyzes a short story of the Salvadoran author Claudia Hernández with the purpose to determine the way in which the fantastic aesthetic is rewritten and appropriated. In the story chosen for this study, the fantastic-allegorical is supported by the absurdity of the situations described, which is extended and updated, acquiring great relevance as means of portraying the multiple realities and situations experienced in Latin America.